Exchange teachers as "another link in binding the [British] Empire" in the interwar years - Kay Whitehead (Historia Social y de la Educación, 2014)
This article focuses on “exchange teachers” from Great Britain plus Australia, Canada, New Zealand and South Africa, these countries constituting the white settler dominions of the British Empire. Participants in the League of Empire’s exchange scheme were mostly white middle class women elementary teachers. Reports of their work in newspapers and magazines show that they used whiteness as a strategy to differentiate the lands and peoples they encountered during their year-long overseas appointment, as well as their experiences of education in government school systems that were underpinned by race thinking. At the same time, they affirmed the British Empire and white settler national identities. Ultimately, exchange teachers were implicated in a transnational politics of whiteness binding the white settler dominions to each other and to the imperial centre in the interwar years.